135 Band 7 leadership development programme. (December 2018) - Robertson, S; Sutton, E
Abstract : Within previous research, to examine the role of ward managers, it was acknowledged that these positions were pivotal, vital, and extremely influential within the trust. Therefore recommendations were made to implement a development programme to enhance clinical leadership skills and to enable band 7 nurses within their role. Listening events with band 7 nurses were held to understand the role and the challenges, matron engagement was sought to provide a further understanding of their requirements and the programme was designed to meet the learning outcomes outlined within this process. The programme aimed to enable band 7 nurses to understand themselves and the impact they have on others; to explore their role as a leader of people and the relationships they build in doing so. Explore their role in staff retention; staff motivation, creating the right climate for learning and development. Deal with stress to develop resilience in themselves and their team. Develop relationships in the wider team and across the hospital and feel less isolated and better supported. At the time of writing this abstract, a total of 62 clinical, band 7 nurses have completed the programme. 100% of participants who had completed the evaluation so far would recommend this programme to colleagues and stated that it is has been an extremely valuable investment of time and money. Benefits include: feeling more competent in their role as a leader, articulating clearer expectations, demonstrating greater confidence in handling difficult conversations and situations, being more proactive and feeling less isolated. The continued aim would be to formulate a sustained approach to the programme, enabling all band 7 nurses to have access to clinical leadership and development. One consideration is to implement this programme for all clinical band 7 clinical practitioners, from all disciplines across the trust, to widen participation focusing on multi-professional education.